PENGARUH KEPUASAN KONSUMEN TERHADAP GETOK TULAR (Studi Empiris: Wisatawan Mancanegara Pantai Kuta-Bali) - Chandra Wibowo Widhianto; Henilia Yulita (Jurnal Hospitality dan Pariwisata, 2017)
Bali is a tourism that is recognized by the whole world in natural beauty and the thickcultural richness. Kuta Beach-Bali is also one of the best ten beaches in the world(Made, 2010). This research took the title "THE INFLUENCE OF CUSTOMERSATISFACTION TO WORD OF MOUTH" (the empirical study: foreign tourists KutaBeach - Bali). The data analysis technique that is looking for a causal effect betweendependent variables and independent variables. Data analysis was conducted on 75respondents who are worldwide tourists visiting Kuta Beach in Bali. The type ofresearch used is explanation associative. The results obtained by the correlationcoefficient (R2) of 0.865, which means that the influence of independent variables X(word of mouth) to Y (satisfaction) is equal to 86% and the rest 14% influenced byother factors outside the model.Keywords: customer satisfaction, word of mouth